HIPPOWONDERS - Samuel, Christina Grace; Lachumanan, Ilakieya; Muniandy, Pavithrra Naikar; Ab Rahman, Aesyah Hawani; Kandasamy, Moganashwari (Universiti Teknologi MARA, Negeri Sembilan, 2025)
HIPPOWONDERS is an educational innovation designed to enhance story writing skills among upper primary students (Years 4 to 6). The goal is to make creative writing more engaging, structured, and accessible through the integration of physical and digital learning tools. The innovation features three key components: flashcards, a dedicated website, and a multi-level quiz. The flashcards, which focus on idioms and expressions, are used during face-to-face classroom sessions to enrich vocabulary and foster expressive language. The website acts as a central hub, containing story writing notes, links to a three-level online quiz, a Padlet space for students to upload their creative works, a Google Form for user feedback, and printable worksheet and flashcard templates for students who wish to use them independently. By combining traditional learning tools with interactive digital platforms, HIPPOWONDERS supports students in developing coherent story structures and imaginative content. This innovation not only promotes independent learning but also encourages peer sharing and reflection, ultimately nurturing confident and creative young writers.